The effects of myricitrin and vitamin E against reproductive changes induced by D-galactose as an aging model in female mice: An experimental study - Mina Omidi; Akram Ahangarpour; Seyed Ali Mard; Layasadat Khorsandi (Shahid Sadoughi University of Medical Sciences, 2019)
Background Aging is accompanied by decreasing general function in the cells and tissues. D-galactose (D-gal) induces aging and plays a role in the pathogenesis of it. Myricitrin is a plant-derived antioxidant. Objective The present study was performed to evaluate the effects of myricitrin on antioxidant defense, sex hormone levels, uterus, and ovarian histology in D-gal-induced aging female mouse model. Materials and Methods In this experimental study, 72 female adult NMRI mice, weighing 30-35 gr, 3-4 months old, were randomly divided into six groups (n = 12/each): (I) Control (vehicle; normal saline), (II) D-gal at 500 mg/kg/d for 45 days, (III-V) D-gal + myricitrin-treated groups (these groups received myricitrin at 5, 10, and 20 mg/kg/d, and (VI) D-gal + 100 mg/kg/d vitamin E orally for the last 28 days. The antioxidant indices were done on the basis of colorimetric method, and sex hormone levels were measured by using enzyme-linked immunosorbent assay kits. Histological assessment of the uterus and ovaries were also evaluated. Results D-gal impaired the estrous cycle, also degenerative changes occur in the ovarian follicles and damage to the uterus and ovarian tissue occurs. In D-gal group, the level of sex hormones (p = 0.03) and the total antioxidant capacity (p = 0.002) decreased, while the level of malondialdehyde and gonadotropins increased (p = 0.03). Myricitrin at lower doses and vitamin E ameliorated the D-gal effects. Conclusion These findings suggest that myricitrin at low doses can effectively prevent D-gal-induced oxidation and aging in mice. The effect of myricitrin was equivalent and sometimes better than vitamin E.